The Experiences of International Teaching Assistants in the US Classroom: A Qualitative Study - Adebayo, Comfort Tosin; Allen, Mike (Journal of International Students, 2020)
Most research focusing on the challenges that international teaching assistants (ITAs) encounter in U.S. classrooms employs a linguistic perspective. The present study furthers that research by examining other challenges unique to ITAs, through the lens of an intercultural competence framework. Through individual interviews with 15 ITAs, the study highlights the challenges related to competencies in knowledge and skills faced by ITAs in U.S. classrooms. Findings reveal that knowledge about the U.S. education system, expectations of the classroom culture, and assumptions about student–instructor relationships pose the greatest difficulties. Additionally, the ability of an ITA to demonstrate communication skills remains a significant challenge, including the negative perception of speaking with a foreign accent and selecting effective word choices to accurately represent content. The study findings present practical implications for training ITAs for their pedagogical duties at U.S. colleges.